Turn of the Screw: Political and epistemic insurgency of social movements in Bolivia - Tórrez, Yuri (2016)
The article aims to provide a reflection about the resurgence of collective action in the form of (new) social movements in Bolivia, an action that marks more than a contestary response to the hegemonic models, in bogue. These movements not only are revealing themselves as political-ideological subjects with the capacity of generating alternative proposals to the hegemonic models, but also with an epistemic capacity to question the basic suppositions the hegemonic order.